TEKS GEGURITAN DHARMA STHITI ANALISIS AMANAT - Sudarsana, I Wayan (Humanis; Volume 9. No. 3. Desember 2014, 2014)
This study discusses the traditional Balinese literature shaped geguritan entitled "Geguritan Dharma Sthiti". Geguritan Dharma Sthiti contains the basic teachings of Hinduism truth as a spiritual moral reflection. The purpose of this study is to determine the mandate which is contained in this geguritan. Methods and techniques used are divided into three stages, namely (1) phase which refers to the provision of data using reading methods, supported by technical translation and recording techniques, (2) the stage of data analysis which uses qualitative methods supported by descriptive analytical techniques, and (3) stage presentation of the analysis results which uses informal methods as well as assisted with the deductive and inductive intellection. The results achieved in this study, is the appearing succession gained in revealing the author of the mandate contained in this geguritan; karmaphala, dharma sthiti, and catur warga.
Keywords: Mandate, Geguritan, and Dharma Sthiti